2019
DOI: 10.1186/s12884-019-2492-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus and associated factors among women attending antenatal care at Gondar town public health facilities, Northwest Ethiopia

Abstract: Background Globally, Gestational Diabetes Mellitus (GDM) is rising, but it is a neglected health threat to mothers and their children in low resource countries. Although, GDM is known in Ethiopia, information regarding it remains scarce by recent diagnostic criteria. Therefore, this study aimed to determine the prevalence of GDM and associated factors among women attending antenatal care at Gondar town public health facilities, Northwest Ethiopia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 62 publications
7
73
6
1
Order By: Relevance
“…In general, the frequency rate observed in this study was within the universal range varying from 8% to 20.7% among all pregnancies in different populations across the African continent and the global range of 3 to 16% across the world [14]. More on the frequency are the disagreeing findings from studies conducted in Rwanda (8.3%) [17], Tanzania (5.6%) [15], Egypt (8%) [18], and Nigeria (8.6%) [19] which obtained a lower frequency than what was observed in our study and that which was reported by the Management Sciences for Health [20] who conducted a study of hyperglycaemia in pregnancy among urban women in Tigray, Northern Ethiopia, and obtained a frequency of 15.8%. The main reason for the high frequency of gestational hyperglycaemia in this study setting might have been due to the fact that the lower cut-off points for fasting plasma glucose (FPG) were used as required in the updated diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 89%
“…In general, the frequency rate observed in this study was within the universal range varying from 8% to 20.7% among all pregnancies in different populations across the African continent and the global range of 3 to 16% across the world [14]. More on the frequency are the disagreeing findings from studies conducted in Rwanda (8.3%) [17], Tanzania (5.6%) [15], Egypt (8%) [18], and Nigeria (8.6%) [19] which obtained a lower frequency than what was observed in our study and that which was reported by the Management Sciences for Health [20] who conducted a study of hyperglycaemia in pregnancy among urban women in Tigray, Northern Ethiopia, and obtained a frequency of 15.8%. The main reason for the high frequency of gestational hyperglycaemia in this study setting might have been due to the fact that the lower cut-off points for fasting plasma glucose (FPG) were used as required in the updated diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 89%
“…This prospective cohort study was part of a larger project, where similar methodology was used in previous published article elsewhere. 15 time, and were followed until 6-12 weeks after delivery. Pregnant women who had pre-existing or overt diabetes, chronic diseases, or on medications that might affect glucose metabolism (steroids, β-adrenergic agonists, antipsychotic drugs) at commencement were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…As described earlier among 1027 pregnant women, 131 (12.8%) were diagnosed with GDM. 15 All women with GDM were invited to participate in the study and their glucose status was evaluated at 6-12 weeks post partum.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, for the baseline survey, about 1,110 study participants were recruited at the beginning of the study and a total of 1027 participants completed the GDM screening enrolled for this cohort study to increase the power of the study. A detail of the study sample is provided elsewhere [33].…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%